Rebuilding a Statistical Apparatus at a Critical Juncture: Argentina and Brazil, from the Great Depression to the Post-World War II period - Daniel, Claudia Jorgelina (2017)
Amidst the political and economic tensions that culminated in World War II, the Brazilian and Argentine states embarked within a few years of each other on significant reforms of their statistical services. In Brazil, the reform gave rise to a new and completely original statistical institution. Argentina, under the pressure of similar statistical challenges, launched a number of failed reorganization attempts. The goal of this article is to analyze and compare the restructuring of both statistical apparatuses. This paper explores how the pillars of the edifice of public statistics in each country were historically constructed, in order to understand the basis of its social legitimacy and credibility.